2022
DOI: 10.3390/diagnostics12112848
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-10 Expression Is Increased in Endometriosis and Adenomyosis and Mislocalized in Ectopic Endometriosis

Abstract: Claudins, as the major components of tight junctions, are crucial for epithelial cell-to-cell contacts. Recently, we showed that in endometriosis, the endometrial epithelial phenotype is highly conserved, with only minor alterations. For example, claudin-11 is strongly expressed; however, its localization in the endometriotic epithelial cells was impaired. In order to better understand the role of claudins in endometrial cell-to-cell contacts, we analyzed the tissue expression and localization of claudin-10 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Similarly, we found a high abundance (~98%) of claudin-10 in nearly all endometrial and endometriotic glands, but no differences in the claudin-10 positive endometrial glands between cases with and without endometriosis [57]. A significantly higher expression of claudin-10 was detected in the ectopic endometrium of deep infiltrating and ovarian endometriosis [57]. Interestingly, a shift in claudin-10 from a predominant apical localization in the eutopic endometrium to a more pronounced basal/cytoplasmic localization in the ectopic endometria of all three endometriotic entities (ovarian, peritoneal, deep infiltrating) was observed.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similarly, we found a high abundance (~98%) of claudin-10 in nearly all endometrial and endometriotic glands, but no differences in the claudin-10 positive endometrial glands between cases with and without endometriosis [57]. A significantly higher expression of claudin-10 was detected in the ectopic endometrium of deep infiltrating and ovarian endometriosis [57]. Interestingly, a shift in claudin-10 from a predominant apical localization in the eutopic endometrium to a more pronounced basal/cytoplasmic localization in the ectopic endometria of all three endometriotic entities (ovarian, peritoneal, deep infiltrating) was observed.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to two reports that described an impaired expression of claudin-3 in endometriosis [54,55], we recently found an unchanged protein localization in the eutopic endometrium with and without endometriosis and also in the ectopic endometrium [56] which might be due to different fixation protocols used. Similarly, we found a high abundance (~98%) of claudin-10 in nearly all endometrial and endometriotic glands, but no differences in the claudin-10 positive endometrial glands between cases with and without endometriosis [57]. A significantly higher expression of claudin-10 was detected in the ectopic endometrium of deep infiltrating and ovarian endometriosis [57].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…[21] In our study, we evaluated the immunostaining score for NGAL expression for the first time in the literature and found that NGAL expression was significantly higher in endometriosis cases than in the control group. As an example of the immunohistochemical scoring study similar to our study, Löffelman AC et al [22] investigated the expression of Claudin 10 in a study Early diagnosis and treatment of endometriosis both prevent the development of malignancy and endometriosis-related complications such as infertility and pain. Therefore, it is important to establish the diagnosis with new, rapid and noninvasive biomarkers.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, we evaluated the immunostaining score for NGAL expression for the first time in the literature and found that NGAL expression was significantly higher in endometriosis cases than in the control group. As an example of the immunohistochemical scoring study similar to our study, Löffelman AC et al [ 22 ] investigated the expression of Claudin 10 in a study on human endometrium, endometriosis and adenomyosis tissue samples. Claudins are the major component of tight junctions and play a role in the escape of cancer cells out of the tissue.…”
Section: Discussionmentioning
confidence: 90%